Disparity in Opportunities: Is It Harder to Match Into Plastic Surgery Residency Without a Home Plastic Surgery Division?. Issue 4 (16th October 2021) - Baghchechi, Mohsen; Oviedo, Parisa; McLean, Paige; Dean, Riley; Dobke, Marek
Abstract : Supplemental digital content is available in the text. Abstract: Medical students pursuing plastic surgery training must overcome multiple challenges to successfully match in such a highly coveted subspecialty. This adversity is amplified in applicants from medical schools without a home plastic surgery residency program and academic division. There is a paucity of data on the advantage of medical students applying from an institution with a home residency program. Applicant data from the past 5 years were accessed from the Association of American Medical Colleges Electronic Residency Application Services statistics form. Individual home programs of successfully matched applicants were collected from plastic surgery residency websites. A survey was distributed to 32 students pursuing specialty residencies from home medical schools without a plastic surgery residency. Evaluation of a subset of incoming plastic surgery interns revealed that 72% of matched applicants attended home medical institutions with plastic surgery residency programs. Seventy-seven percent of survey respondents felt strongly that students at institutions with home residency programs had a significant advantage. The current COVID pandemic is changing the landscape of subinternships and bringing to light the disadvantage students face without home residency programs. The development of virtual subinternships, online mentorship, and selection of students for subinternships from geographic areas without home programs may help address some disparities in educational opportunities. Continuing these virtual programs and offering preferential help to disadvantaged medical students permanently is an avenue for the field of plastic surgery to be a leader in diversity and inclusion.